PENGEMBANGAN POTENSI WISATA EMBUNG SUMBERAGUNG SEBAGAI DAYA TARIK WISATA MELALUI PEMENUHAN ASPEK 4A - Patricia, Kezia Angelin; Pertiwi, Tri Kartika (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2023)
A tourism potential that can become a tourist attraction should have a tourism 4A Attraction, Accessibility, Amenities, Ancillary Service component which can be the first step in tourism development. The problem faced in the development of this tourism potential is a tourism potential area with inadequate facilities, even not maintained and neglected even though this place has been used several times as a place for competitions such as fishing competitions and trail motorbike competition areas. Implementation methods used by conducting surveys and interviews. Each data collected is carried out by observing directly to tourism potential areas and conducting interviews with village officials, as well as collecting documentation to collect secondary data. This implementation begins with conducting a survey in the Sumberagung Reservoir area to find out what things are lacking and can be carried out to fulfill the 4A aspect as one of the components so that the tourism potential is feasible to be used as tourism. The first is carried out from Aspect 4A. It is hoped that the service that has been carried out will continue to be developed by the tourism manager by promoting and continuing to add facilities that can support Embung Sumberagung tourism.